Analisa Penerapan Produk Siber Dalam Kasus Penyalahgunaan Narkotika - Miftah, Farrah (Wajah Hukum, 2024)
Narcotics abuse in Indonesia is one of the things that is deemed necessary to be dealt with immediately and even to be detected early through prevention of narcotics abuse itself. Narcotics basically have their own benefits if they can be used properly, especially in the health sector. However, when it reaches the realm of narcotics abuse, it can already be categorized as an act against the law. In this study the authors discuss the role of cyber in the judge's decision on narcotics abuse cases, in this case the discussion focuses on how the location and role of cyber in handling it for the settlement of narcotics abuse cases. This is because cyber is an innovative solution if its use can be utilized in this case and in the current era. The purpose of this study is to determine the role of cyber products in narcotics abuse cases, especially from a legal perspective. The research method used in this study is a normative juridical research method that uses a statutory approach and will get conclusions in the form of an analysis of the role of cyber law in cases of drug abuse. The results of this study found that there were several links to the role of cyber products in solving narcotics abuse cases, especially in the scope of evidence.